Using 3D Models to Investigate the Impaired Wound Healing Functions of Diabetic Foot Ulcer-Derived Fibroblasts. - Maione, Anna. (2017)
Abstract: Diabetic foot ulcers (DFU) are a serious and debilitating complication of diabetes. Unfortunately, many DFUs are refractory to current treatments and result in amputation. In order to develop more effective therapies, we must better understand how cellular dysfunctions mediate the pathobiology of chronic wounds. However, conventional monolayer cultures and in vivo wound models have been limited in their ability to recapitulate human chronic wound healing. Thus, we have adapted a panel of three-dimensional (3D), tissue-engineered models to study the performance of chronic wound-derived cells. We used these models to investigate the ability of DFU-derived fibroblasts to perform critical wound healing functions compared to fibroblasts isolated from site-matched diabetic and non-diabetic patient skin samples. Incorporation of patient-derived fibroblasts into the 3D tissue models showed that DFU-derived fibroblasts are less able to stimulate angiogenesis, induce increased keratinocyte proliferation, are less able to support re-epithelialization and produce an aberrant extracellular matrix (ECM). These results not only provided insight into chronic wound fibroblast dysfunctions, but also demonstrate that these models mimic important characteristics of DFUs that have not been reproduced in vitro. Having established the biological relevance of these models, we demonstrated the ability to manipulate them to address specific research questions such as investigating the effects of growth factor stimulation on ECM production or the effects of hyperglycemia on angiogenesis. Taken together, this work provides evidence for the role of fibroblast dysfunctions in chronic wound healing and develops powerful tools for investigating the mechanisms underlying DFU pathogenesis and discovering potential therapeutic targets.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: Jonathan Garlick.; Committee: Charlotte Kuperwasser, John Castellot, Gary Sahagian, and Aristidis Veves.; Keyword: Cellular biology.